Struktur Komunitas Zooplankton di Perairan Desa Mangunharjo Kecamatan Tugu Semarang - Ana, Desy Lasri; Endrawati, Hadi; Santosa, Gunawan Widi (977-2407769)
Mangunharjo village waters is located in Subdistrict Tugu, Semarang is the waters close to densely populated settlements. Household waste and industrial waste will affect water quality and community structure of zooplankton in waters. The aims of the research was to find out the community structure of Zooplankton in the village Mangunharjo Waters, subdistrict Tugu, Semarang. The method in this research was case study method with the exploratory nature of data collection used Sample Survey Method. The location was set as a research location was the location 1, as the areas of a body of a river, Location 2 as the river estuaries, and Location of 3 as ocean waters. Sampling was performed every 2 weeks for 5 times the sampling making use planktonnet with mesh size 45 Î¼m. Sampling was carried out vertically at high tide and low tide began from May to July 2012. The results obtained 49 genera at high tide, while at low tide obtained 44 genera. Abundance obtained when the observation was an average of 17.90 specs/L at high tide, and at low tide the average gained 20.49 specs/L. Diversity of zooplankton an average of 2.20 obtained at high tide, and an average of 2.13 obtained at low tide. Homogeneity obtained average for sampling at the time of high tide and low tide with the same value at 0.56. The index domination at high tide and low tide also have the same value, the average 0.44.